Dynamics of vapor plume in transient keyhole during laser welding of stainless steel: Local evaporation, plume swing and gas entrapment into porosity. (July 2016) - Pang, Shengyong; Chen, Xin; Shao, Xinyu; Gong, Shuili; Xiao, Jianzhong
Abstract: In order to better understand the local evaporation phenomena of keyhole wall, vapor plume swing above the keyhole and ambient gas entrapment into the porosity defects, the 3D time-dependent dynamics of the metallic vapor plume in a transient keyhole during fiber laser welding is numerically investigated. The vapor dynamical parameters, including the velocity and pressure, are successfully predicted and obtain good agreements with the experimental and literature data. It is found that the vapor plume flow inside the keyhole has complex multiple directions, and this various directions characteristic of the vapor plume is resulted from the dynamic evaporation phenomena with variable locations and orientations on the keyhole wall. The results also demonstrate that because of this dynamic local evaporation, the ejected vapor plume from the keyhole opening is usually in high frequency swinging. The results further indicate that the oscillation frequency of the plume swing angle is around 2.0–8.0 kHz, which is of the same order of magnitude with that of the keyhole depth (2.0–5.0 kHz). This consistency clearly shows that the swing of the ejected vapor plume is closely associated with the keyhole instability during laser welding. Furthermore, it is learned that there is usually a negative pressure region (several hundred Pa lower than the atmospheric pressure) of the vapor flow around the keyhole opening. This pressure could lead to a strong vortex flow near the rear keyhole wall, especially when the velocity of the ejected metallic vapor from the keyhole opening is high. Under the effect of this flow, the ambient gas is involved into the keyhole, and could finally be entrapped into the bubbles within a very short time (<0.2 ms) due to the complex flow inside the keyhole. Highlights: Violent local evaporation leads to a complex multiple directions vapor flow. The swing of the ejected vapor plume is closely related to the keyhole instability. The plume swing oscillation frequency at the keyhole opening is 2.0–8.0 kHz. The possible process of the ambient gas entrapment into a bubble is observed.